PROFITABILITY, CAPITAL STRUCTURE, AND LIQUIDITY AS DETERMINANTS OF FINANCIAL DISTRESS IN CONSUMER NON-CYCLICALS - Nicholas Kevin; Liana Susanto (Graduate Program of Universitas Tarumanagara, 2026)
This study’s purpose is to analyze the effect of profitability, capital structure, and liquidity on financial distress among consumer non-cyclicals sector firms listed on the BEI during 2022–2024. The urgency of this study lies in the strategic role of consumer non-cyclicals companies in providing basic needs, yet still facing post-pandemic challenges such as rising raw material costs, fluctuating consumer purchasing power, and global supply chain uncertainty. Theoretically, financial variables such as profitability, capital structure, and liquidity are considered essential predictors of potential bankruptcy. This research applies a quantitative design using secondary data from 64 company observations, analyzed with IBM SPSS Statistics 31. The outcome indicates that both liquidity and profitability contribute significantly to lowering financial distress, while capital structure shows no significant effect. This indicates that firms with higher Return on Assets (ROA) and Current Ratio (CR) tend to have higher Z-Scores, reflecting stronger financial health. Conversely, Capital Structure (DER) cannot serve as a reliable predictor since its effect is inconsistent across firms. In conclusion, the key factors strengthening financial resilience in consumer non-cyclicals companies are profitability and liquidity, while capital structure plays a relatively weak role.